2003
DOI: 10.1243/095440903769012894
|View full text |Cite
|
Sign up to set email alerts
|

The effect of proximity of a rail end in elastic-plastic contact between a wheel and a rail

Abstract: This paper investigates the effects of a free rail end on the contact stress distribution near the rail end by employing elastic-plastic finite element methods. The contact elements were used to simulate the interaction between a wheel and a rail. A plane strain model was used in this study. Variations in contact stress fields at various contact points near the rail end were compared. The availability of the Hertz contact theory in the region near the rail end was also investigated. The numerical results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…early material deterioration. The loss of stiffness closer to the free edge shown in Figure 8 is in agreement with the results discussed in Hanson and Keer (1989) and Chen (2003). Figure 9 shows the equivalent stress field close to the end at load F. The optimal maximum von Mises stress is approximately 0.688 P 0 , reduced from 0.692 P 0 for the one in the original shape with a sharp corner.…”
Section: Rail Edge Rail Symmetric Surfacesupporting
confidence: 86%
See 1 more Smart Citation
“…early material deterioration. The loss of stiffness closer to the free edge shown in Figure 8 is in agreement with the results discussed in Hanson and Keer (1989) and Chen (2003). Figure 9 shows the equivalent stress field close to the end at load F. The optimal maximum von Mises stress is approximately 0.688 P 0 , reduced from 0.692 P 0 for the one in the original shape with a sharp corner.…”
Section: Rail Edge Rail Symmetric Surfacesupporting
confidence: 86%
“…The unsupported rail edge under a static wheel load was examined by Chen and Kuang (2002) for frictionless contact using a three-dimensional FEM and by Chen (2003) using a two-dimensional elastic-plastic plane strain FEM. The contact pressure and stress variations in the proximity of the free edge were reported, with the maximum von Mises stress increasing and shifting to the edge corner as the wheel moved to the rail end.…”
Section: Introductionmentioning
confidence: 99%
“…A peak pressure of 2000 MPa on IRJs was used elsewhere. 9 In the ABAQUS mesh module, eight-node fully integrated tri-linear brick elements (C3D8) were considered for all components in the solid modelling zone. This type of element was considered because it is widely used in elastic-plastic material deformation.…”
Section: Global Modelling Strategymentioning
confidence: 99%
“…2,[5][6][7][8] However, only a few research studies have been conducted considering GRJs. Initially, Chen 9 employed an elastic-plastic plain strain finite element method to investigate the effects of a free rail end on wheel/rail contact stress distribution. The simulated results suggested that contact stress distributions around the rail end are sensitive to the contact distance from the free end.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation